Altered subcellular reactions to stress after a long-term human exposure to antarctic condition - Moiseyenko, Ye.; Rozova, K. (Journal of Education, Health and Sport, 2024)
Medical research in Antarctica opens up new horizons to study individual health and reactions under stress and unusual environmental conditions. A long stay in Antarctica can evoke reactions associated with adaptation to hypoxia and mitochondrial dysfunction, determined by a set of molecular-genetic mechanisms. The aim was to study the changes in platelet ultrastructure in Antarctic winterers under hypoxic loading, and the ultrastructure of mitochondria (MT) of leukocytes in winterers, depending on the length of exposure to Antarctic conditions and number of expeditions participated. We included to the study 24 winterers, who once stayed in Antarctica during 1 year (group 1), 3-4 one-year stays (group 2), and 5-7 one-year stays (group 3). The control group included 8 men, who were not exposed to adverse environmental factors and never visited Antarctica. We assessed the ultrastructure of platelet and leukocytes before and after the hypoxic loading. The background characteristics of the ultrastructure of platelets and leukocytes of winterers. Significant changes developed in the platelet and leukocytes mitochondria ultrastructure after hypoxic loading. The severity of changes in leukocyte mitochondria correlated with number of expeditions participated, and manifested by development of autophagy, apoptosis up to irreversible organelle changes, a partial or complete vacuolization, excessive swelling of organelles after 1 year stay, 3-4, and 5-7 one-year expeditions respectively. So, a long exposure to Antarctic conditions is associated with mitochondrial dysfunction.